PROYECTO CURRICULAR DE LICENCIATURA EN ELECTRÓNICA UNA VISIÓN SINTÉTICA - Urrea Ospina, Iván Darío (Tecné, Episteme y Didaxis: TED, 2000)
The present article has as main intention to present a summary of the structure of the Curricular Project of Licentiate in Electronics that was presented to the National Council of Accreditation for previous accreditation, with the purpose of carrying out its popularization and presentation especially to the national academic community. Next they are presented the context in the one which you development the proposal, the relating epistemológico, pedagogic and didactic, the curricular proposal and the investigation component from which the process of formation of Graduates is approached in Electronic. ln the final part a description of the project is presented as for its institutional characteristics, objectives and the competitions that he/she hopes fo achieve in the students that participate in its development